AN APPROACH FOR THE MULTI-CRITERIA DERIVATION OF LIGHTWEIGHT POTENTIAL. (May 2020) - Laufer, F.; Roth, D.; Binz, H.
Abstract: Lightweight potential is a powerful indicator – but not as powerful as it could be. Current methods for analyzing a product's potential to be reduced in mass only deal with a few of the most important criteria for lightweight design. This paper presents an approach transferring cost-benefit analysis to the holistic derivation of lightweight potential. The approach is able to deal with different types of criteria supporting the designer in indentifying the most promising components for mass reduction. An evaluation example is given showcasing a tooling machine.